When I found you - Novak, Brenda (Novak, Brenda. Silver Springs., 2021)
After everything she worked for is destroyed, pediatrician Natasha Gray is determined to build a new life. Divorced, bankrupt and suddenly a single mom, she's ready to start over in Silver Springs on her own. She certainly doesn't need help from Mack Amos, the man who's already broken her heart twice. Although Mack has had feelings for Tash since they first met, too many things have stood in the way. He's always given her the support she needs ... Even if the desire he wrestles with threatens to undermine his intentions"--